EASTERN GALICIA IN THE PERIOD OF THE FIRST WORLD WAR: EUROPEAN HISTORIOGRAPHY - Баран, Игорь (SWorldJournal, 2021)
The first world war that brought to the European people enormous human victims and destructions always occupied one of key places in researches of scientists of many countries. In the article paid attention to the analysis of пра scientific researches o